STUDI TENTANG TINGKAT EROSI TEBING SUNGAI DI ALIRAN BATANG PALANGAI KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Yanti, Elmi; Juita, Erna; Farida, Farida (STKIP PGRI Sumbar, 2013)
This research to get information about the erosion rate in the flow of the DAS Batang Palangai Ranah Pesisir District Pesisir Selatan regency. The method used in this research is descriptive method, sampling method in this study is the method of sample areas (sampling area), where the unit of measurement is the area along the Batang Palangai. Erosion rate measured by the flow velocity, slope, vegetation, and exposed rocks. The results show as follows: (1) the erosion of the study area based on the flow velocity is generally high at 44.22 to 83.33 cm / sec, so the potential for stream bank erosion, (2) the erosion of the study area based on potential general slope riverbank erosion because class II, (3) the erosion of the study area based on potential vegetation land cover enough river bank erosion. Vegetation cover consists of grass, coconut and palm oil. This situation makes the vegetation cover along the Batang Palangai cannot withstand the erosion of river banks and (4) The erosion of the study area based rock will potentially exposed river bank erosion on stream Batang Palangai